Analisis Kapasitas Parkir Kendaraan di Kampus Universitas Muhadi Setiabudi, Kabupaten Brebes - Rizqi Aji Saputra; Muhamad Yunus; Toto Mulyono (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
As the center of academic activities of Muhadi Setiabudi University with 101 lecturers, 1266 students and 94 employees must be supported by adequate parking infrastructure. Parking is an important infrastructure in an activity. One of the problems in parking is the lack of adequate parking space. For this reason, it is necessary to evaluate the characteristics of parking in the campus area. The evaluation results found parking characteristics at the location in the form of: motorcycle parking volume of 347 vehicles and cars of 28 vehicles. The maximum parking duration for motorbikes is 195,089 minutes and cars is 185,591 minutes. The maximum accumulated value of motorcycle parking is 267 vehicles and cars are 18 vehicles. The maximum static capacity on the motorcycle is 922 vehicles while for cars it is 41 vehicles. The maximum parking index on motorcycles is 89% as well as on cars is 130%. The maximum turnover on motorcycles is 1.16 times and for cars 2.16 times. The maximum parking space requirement on motorcycles is 294 vehicles, on cars is 20 vehicles. From the calculation results, it can be concluded that the capacity of the existing parking lot for motorbikes is adequate, but for cars it is not adequate.